2022
DOI: 10.3390/ma15176008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Methodology for the Quality Management of Duplex Stainless Steels

Abstract: The use of traditional materials leads to failures and breakdowns of expensive equipment, so advanced materials are needed that can provide reliable and durable solutions. The ability to control the quality of duplex stainless steels (DSSs) can greatly help with the development of new compositions or choosing existing DSSs. In this case, it is necessary to consider the final consumer properties—corrosion resistance and mechanical properties, which depend on the phase composition, contamination with non-metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This inclusion was found inside a cleavage facet, which showed higher chromium and lower nickel content, suggesting α-phase (ferrite cleavage facet) [49]. Performing an EDX analysis on the inclusion, it was confirmed that it was a TiN nonmetallic inclusion (NMI) (see Figure 10b) [61,62]. This type of TiN NMI has been seen to promote higher corrosion susceptibility in duplex stainless steel, leading in some cases to the promotion of TG-SCC [63,64].…”
Section: Energy-dispersive X-ray Spectroscopy (Edx)mentioning
confidence: 90%
“…This inclusion was found inside a cleavage facet, which showed higher chromium and lower nickel content, suggesting α-phase (ferrite cleavage facet) [49]. Performing an EDX analysis on the inclusion, it was confirmed that it was a TiN nonmetallic inclusion (NMI) (see Figure 10b) [61,62]. This type of TiN NMI has been seen to promote higher corrosion susceptibility in duplex stainless steel, leading in some cases to the promotion of TG-SCC [63,64].…”
Section: Energy-dispersive X-ray Spectroscopy (Edx)mentioning
confidence: 90%
“…In an earlier work by the authors, three steels deoxidized with titanium, aluminum, and rare earth metals were studied and the effect of deoxidizers on resistance to pitting and crevice corrosion was shown [2]. However, the nature of NMIs was not sufficiently studied.…”
Section: This Workmentioning
confidence: 99%
“…These steels are used to produce various castings: fittings, casings and the moving parts of pumps. Such local corrosion damage occurs even if the chemical composition and heat treatment provide the required quality of the structure [2,3]. Localization of pitting occurs near non-metallic inclusions (NMIs) [4][5][6][7][8], formed during the melting, casting and solidification of these steels [4,5,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations